Effects of Oxidative Stress on Alzheimer's Disease, Haematological Perspective - Tengku Muhammad Ariff, Raja Hussin; Ahmad Zubaidi, A.latif; Nordin, Simbak; Atif Amin, Baig (2018)
Alzheimer disease (AD) is considered among the most important neurodegenerative disorder in elderly individuals. AD patients ha higher oxidative stress as compared to normal people with a higher susceptibility to health problems. Oxidative stress Results into several disorders including AD. Oxidative stress in AD patients may lead to abnormal red blood cells (RBCs) indices and elevated white blood cells (WBCs) count. Oxidative stress in AD patients can lead to massive destruction of red blood cells (RBCs). The br and the gastrointestinal system are intimately connected, as one system. The brain has a direct impact on the GI tract. A stressfu brain can send signals to the gut, just as a troubled intestine can send signals to the brain. Therefore, oxidative stress in AD patie can be reason for hindering the breakdown and assimilation of food for energy and nourishment. This malabsorption can then lea a reciprocal negative effect on oxidative stress and also can be another cause of anaemia due to malabsorption of minerals and vitamins that are important to erythropoiesis. Therefore this review article is designed to unearth the effect of oxidative stress in A patients and incite leading researchers to generate database that will help in understand the relationship between oxidative stress and haematological parameters especially in AD patients.